Long‐term outcome after limited cortical resections in two cases of adult‐onset Rasmussen encephalitis. Issue 5 (4th April 2014) - Villani, Flavio; Didato, Giuseppe; Deleo, Francesco; Tringali, Giovanni; Garbelli, Rita; Granata, Tiziana; Marras, Carlo Efisio; Cordella, Roberto; Spreafico, Roberto
Summary: Rasmussen encephalitis (RE) is a progressive inflammatory disorder characterized by brain hemiatrophy, unilateral focal deficits, and drug‐refractory focal epilepsy. Epilepsia partialis continua (EPC) is a hallmark of the disease. Several immunomodulatory treatments may slow but not halt the disease progression. The treatment of choice still relies on surgical hemispheric disconnection, which is burdened by heavy neurologic morbidity. More limited cortical resections, although more tolerable, are usually considered to be, at best, only transiently effective in RE. Hemispheric disconnections may be not feasible when neurologic functions are preserved and the dominant hemisphere is affected. Adult patients with a milder RE course that preserves neurologic function for a long period are particularly at risk of developing severe deficits after surgery. In this study we present the histories of two patients with adult‐onset RE who have undergone selective cortical resections to control EPC, avoiding, at the same time, the severe postsurgical deficits that may be induced by hemispheric disconnective surgery. The good result obtained on EPC has been stable over a prolonged period; however, this result was not paralleled by the stop of neurologic progression in one of the two cases. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here .